1994
DOI: 10.5014/ajot.48.6.546
|View full text |Cite
|
Sign up to set email alerts
|

Medical Considerations and Practice Guidelines for the Neonatal Occupational Therapist

Abstract: Provision of safe and effective occupational therapy in neonatal intensive care units requires an understanding of neonatal medical conditions and treatment modalities. This article explains basic medical concepts and technology with terminology frequently encountered in neonatal intensive care. Discussions of neonatal thermoregulation, respiratory care, hemodynamic monitoring, and metabolic support are presented as general areas of focus. Equipment usage and precautions are included. Several case studies illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
9
0
3
Order By: Relevance
“…Increasing evidence mandates that neurodevelopmental allied health staff across all disciplines possess higher level qualifications, and have graduated entry into the NICU/SCN environment . In the current study on average, physiotherapists and occupational therapists reported the highest qualifications, with speech pathologists reporting the lowest.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Increasing evidence mandates that neurodevelopmental allied health staff across all disciplines possess higher level qualifications, and have graduated entry into the NICU/SCN environment . In the current study on average, physiotherapists and occupational therapists reported the highest qualifications, with speech pathologists reporting the lowest.…”
Section: Discussionmentioning
confidence: 54%
“…3 Increasing evidence mandates that neurodevelopmental allied health staff across all disciplines possess higher level qualifications, and have graduated entry into the NICU/SCN environment. 3,6,9,10 In the current study on average, physiotherapists and occupational therapists reported the highest qualifications, with speech pathologists reporting the lowest. Rapport 5 surveyed 709 NICUs across the USA: 60% of physiotherapists and occupational therapists had completed or were completing a masters or other advanced course, while 40% had no postgraduate certifications/qualifications.…”
Section: Number Of Unitsmentioning
confidence: 53%
See 1 more Smart Citation
“…Premature infants often have difficulty feeding orally and obtaining enough nutrients for adequate growth (Caretto, Topolski, Linkous, Lowman, & Murphy, 2000;Hunter, Mullen, & Dallas, 1994); coordinating the suck-swallow-breathe triad to prevent aspiration of liquids while feeding (Glass & Wolf, 1998;Mathew, 1988); and operating immature lungs to breathe on their own (Glass & Wolf; Mathew). Immature oral reflexes, high stress levels, reduced oral sensory input, and decreased opportunity to suck as a result of non-oral feedings can all contribute to oral feeding inefficiencies and delayed oral motor development (Anderson, 1986;Case-Smith, 1988;Einarsson-Backes, Deitz, Price, Glass, & Hays, 1994;Hunter et al).…”
Section: Feeding Systemmentioning
confidence: 99%
“…Immature oral reflexes, high stress levels, reduced oral sensory input, and decreased opportunity to suck as a result of non-oral feedings can all contribute to oral feeding inefficiencies and delayed oral motor development (Anderson, 1986;Case-Smith, 1988;Einarsson-Backes, Deitz, Price, Glass, & Hays, 1994;Hunter et al). These experiences can further lead to poor growth and longer hospital stays, as an infant's ability to fully feed by bottle and/or breast is a common criterion necessary for discharge to home (Shaker, 1999).…”
Section: Feeding Systemmentioning
confidence: 99%